Evaluation of Campus Learning and Industrial Work Practice Based on Cipp at The Banten Petrochemical Industry Polytechnic - Rudi Repelita; Nurul Anriani; Yuyu Yuhana (PT. Global Research Collaboration, 2026)
This study examines the effectiveness of the Dual System Education Program at Politeknik Industri Petrokimia Banten within the context of vocational education reform in Indonesia. Adopting a mixed methods sequential explanatory design grounded in a pragmatic paradigm, the research integrates quantitative and qualitative data to evaluate program performance using the CIPP (Context, Input, Process, Product) model. Quantitative data were collected through structured questionnaires distributed to key stakeholders, while qualitative insights were obtained through interviews, focus group discussions, and document analysis. The findings indicate that the program demonstrates strong alignment with national policies and industry needs (context), supported by adequate curriculum design and institutional resources (input). The implementation of work-based learning through industrial training is generally effective (process), although inconsistencies in supervision and evaluation mechanisms remain evident. In terms of outcomes (product), graduates exhibit solid technical competencies; however, challenges persist in soft skills development and employment absorption, reflecting broader labor market mismatches. Overall, the study highlights that while the program has made significant progress in bridging education and industry, its long-term effectiveness depends on continuous curriculum adaptation, modernization of training infrastructure, and strengthened collaboration with industry partners. The integration of the CIPP model with mixed methods provides a comprehensive framework for evaluating vocational education systems and offers evidence-based insights for policy and institutional improvement.